The influence of organizational compassion on Job Crafting: A motivational resource facilitator? - Araújo, Maria Leonor (2022)
This study aimed to analyse the relationship between the perception of compassion at work  (consciousness, empathy, evaluation, response type) and compassionate “actions and organizational  characteristics” on job crafting (increasing structural job resources, increasing social job resources, increasing challenging job demands, decreasing hindering job demands). The study collected quantitative data from 231 professionals from different economic sectors. The results indicated that only the dimensions: “evaluation” and “response type” of the compassion process, as well as compassionate “organizational characteristics”, showed a positive influence in the “increasing structural job resources”, “increasing social job resources” and “increasing challenging job demands”. There was no negative relationship between the dimensions of the compassion process and compassionate “organizational characteristics and actions” in “decreasing hindering job demands”. The mechanisms by which compassion at work could have positive effects on the job crafting processes are presented.